A Survey Or Drug Abuse Prevention Strategies. - Choo, Piang Fong; Ismail, Maznah; Navaratnam, V.; Hoo, See Kong (Pusat Penyelidikan Dadah Kebangsaan, Universiti Sains Malaysia, 1985)
The drug abuse problem began to take hold in Malaysia in 1969 and since then, the-government has been involved in various measures to control the situation.